Media and politics in the Baltic States - Kazakevičiūtė, Inga (Žurnalistikos tyrimai, 2015)
The international scientific conference “Interaction of Media and Politics in the Baltic States” was held at the Faculty of Communication of Vilnius University on 7-8 May 2015. Researchers from universities in Lithuania, Latvia, Estonia, Finland, Sweden, Poland and United Kingdom analysed issues in media policy, propaganda, information warfare, political communication and investigative journalism.